Symmetric and Asymmetric Effect of Crude Oil Prices and Exchange Rate on Bond Yields in Indonesia - Saenong, Zainuddin; Muthalib, Abd Azis; Adam, Pasrun; Rumbia, Wali Aya; Millia, Heppi; Saidi, La Ode (International Journal of Energy Economics and Policy, 2020)
This study aims to examine the symmetric and asymmetric effects of crude oil prices and exchange rate on bond yields in Indonesia. Dubai crude oil prices are used as a proxy for crude oil price data and the IDR/USD exchange rate is used as a proxy for exchange rate. Meanwhile, the 10-year Indonesian bond yields are used as a proxy for bond yields. Data on Dubai crude oil prices, the IDR/USD exchange rate, and the 10-year Indonesian government bond yields are time-series data from January 2007 to April 2019. The results of the test using the ARDL and NARDL models show that (1) in the long-run, neither the crude oil prices nor the exchange rate has symmetric and asymmetric effects on the bond yields, and (2) in the short-run, both of them have symmetric and asymmetric effects on the bond yields. Keywords: crude oil prices, exchange rates, bond yields, ARDL model, NARDL model. JEL Classifications: C120, C130, E310, G150 DOI: https://doi.org/10.32479/ijeep.8878